2018
DOI: 10.1093/cid/ciy552
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exacerbations of Chronic Obstructive Pulmonary Disease With a Low Procalcitonin Concentration: Impact of Antibiotic Therapy

Abstract: For adult patients hospitalized with non-severe AECOPD and low PCT concentrations, antibiotic therapy beyond 24 hours did not improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…41 However, the majority of prescriptions were for short-course (5-10 days) azithromycin therapy which has been shown to offer no benefit in AECOPD. 42…”
Section: Discussionmentioning
confidence: 99%
“…41 However, the majority of prescriptions were for short-course (5-10 days) azithromycin therapy which has been shown to offer no benefit in AECOPD. 42…”
Section: Discussionmentioning
confidence: 99%
“…Доведено, що підвищення рівня ПКТ у сироватці крові відбувається під дією ендотоксинів бактерій і корелює з тяжкістю інфекції [13,14]. Завдяки швидкій імунній відповіді рівень ПКТ зростає вже через 6-12 год після початку запального процесу [15,16].…”
Section: Discussionunclassified
“…PCT threshold values were based on values approved by the US Food and Drug Administration and previous studies-antibiotics were discouraged for PCT levels ≤ 0.25 ng/mL but could be considered for PCT levels > 0.25 ng/mL. 5,8,9 Clinicians were not required to use the algorithm, and the use of clinical judgement was encouraged. The recommended antibiotic therapies were based on previously approved PVAHCS antimicrobial stewardship guidance.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have suggested that PCT may be used in patients experiencing an AECOPD to reduce antibiotic use without impacting rates of treatment failure. [5][6][7][8][9] A majority of these studies have been in the inpatient setting or a combination of inpatient and outpatient settings.…”
mentioning
confidence: 99%